2018
DOI: 10.1111/epi.14013
|View full text |Cite
|
Sign up to set email alerts
|

Delayed myelination and neurodevelopment in male seizure‐prone versus seizure‐resistant rats

Abstract: Relative delays in myelination and neurodevelopment co-occurred in the seizure-prone FAST strain in the absence of seizures. These findings suggest these symptoms are not seizure-induced and may be mechanistically linked to an underlying pathophysiology supporting a predisposition toward developing epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 41 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Although it is nearly impossible to prove that the altered myelination is the underlying cause of increased seizure susceptibility, there is a growing evidence to suggest that altered myelination constitutes part of the mechanism underlying epilepsy. Hypomyelination was observed in TSC1 and epileptic conditions (Carson et al, 2015;Ercan et al, 2017;Larson et al, 2018;Meikle et al, 2007;Peters et al, 2019;Scholl et al, 2017;Schurr et al, 2017;Sharma et al, 2018;Shepherd et al, 2013). Loss of function of genes in ODCs was sufficient to cause spontaneous seizures (Figlia et al, 2017;Lebrun-Julien et al, 2014;McLane et al, 2017;Shi et al, 2018;Wahl et al, 2014).…”
Section: Myelination In Seizure Propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is nearly impossible to prove that the altered myelination is the underlying cause of increased seizure susceptibility, there is a growing evidence to suggest that altered myelination constitutes part of the mechanism underlying epilepsy. Hypomyelination was observed in TSC1 and epileptic conditions (Carson et al, 2015;Ercan et al, 2017;Larson et al, 2018;Meikle et al, 2007;Peters et al, 2019;Scholl et al, 2017;Schurr et al, 2017;Sharma et al, 2018;Shepherd et al, 2013). Loss of function of genes in ODCs was sufficient to cause spontaneous seizures (Figlia et al, 2017;Lebrun-Julien et al, 2014;McLane et al, 2017;Shi et al, 2018;Wahl et al, 2014).…”
Section: Myelination In Seizure Propagationmentioning
confidence: 99%
“…Here, we found that deletion of Atg7 in microglia promotes increased amounts of mature ODCs and myelination markers. Interestingly, hypomyelination was reported in both human TSC1 patients and TSC1-deficient animal models (Carson et al, 2015;Ercan et al, 2017;Larson et al, 2018;Meikle et al, 2007;Peters et al, 2019;Scholl et al, 2017;Schurr et al, 2017;Sharma et al, 2018;Shepherd et al, 2013). Because mTOR signaling and autophagy are connected, the contrasting outcomes are intriguing and perhaps reflect the different cell types in which the mTOR or autophagy signaling is altered.…”
Section: Myelination In Seizure Propagationmentioning
confidence: 99%
“…For instance, the density of myelinated axons in optic tracts and stria medularis appears to be decreased in the kainic acid model [132]. Furthermore, delayed myelination is observed in the brain stem, cerebellum, and cerebral hemispheres in seizure-prone FAST rats on postnatal days 5 and 11 [133]. The expression of MBP protein in the thalamus is also altered in animals with genetic absence epilepsy [134].…”
Section: White Matter Disorders In Animal Models Of Epilepsymentioning
confidence: 99%
“…Developmental delay, a common indicator of abnormal brain development, can manifest as delays in the acquisition of speech and language, motor control (gross and fine), auditory processing, and social communication in humans . Exploratory neurodevelopmental studies in FAST and SLOW strains have revealed developmental delay in FAST rats, observed as delayed physical development (eye opening), neuromuscular development (decreased locomotor activity), and neuromotor and sensory system development (increased latencies to respond to righting reflex, cliff avoidance, and negative geotaxis tests) . These delays were evident within the first two postnatal weeks (PND5‐15), a time period comparable to late third trimester through to 8 months of postnatal age in humans.…”
Section: Fast and Slow Rats—behavioral Phenotypementioning
confidence: 99%
“…Neurodevelopmental trajectory Physical, neuromuscular, neuromotor, and sensory developmental delays - 37 Fear, anxiety, and activity Increased activity in EPM, open field, and restraint paradigms Increased fear, anxiety in EPM [42][43][44][45][46] Impulsive behavior Abnormal sexual assertiveness of FAST rats; rapid latency to mounting Delayed latency to mount potential partner compared to parental strains [48][49][50] Cognitive dysfunction Impaired concept formation, working and reference memory, and easy distractibility in T-maze and MWM - [50][51][52] Social behaviors Abnormal repetitive behaviors; more juvenile-like play fighting behavior…”
Section: Behaviors Fast Rats Slow Rats Referencesmentioning
confidence: 99%